A critical handbook of children's literature - Smith, Jacquelin J.; Coffel, Cynthia Miller (Boston, Massachusetts : Pearson Education, Incorporated, 2013)
A Critical Handbook of Children$1 (Bs Literature, Ninth Edition, gives future teachers, practicing teachers, librarians, and parents many examples of quality children$1 (Bs literature to guide them in choosing the best books for the classroom, library, or home. The Handbook analyzes children$1 (Bs books that showcase positive examples of the literary elements, formats, and genres that are the focus in the field of children$1 (Bs literature. The books are noteworthy children$1 (Bs books, from classics to favorites to just-published titles, all selected as thought-provoking, important, or motivating choices.s
Chapter1. Literature: What is it? -- Chapter2. Issues and fundamental change in children's literature -- Chapter3. Picture books -- Chapter4. Genre in children's literature -- Chapter5. Character -- Chapter6. Plot -- Chapter7. Setting -- Chapter8. Point of view -- Chapter9. Style and tone -- Chapter10. Theme -- Chapter11. From rhyme to poetry -- Chapter12. Biography -- Chapter13. Information books -- Chapter14. A lifetime of reading .
Includes bibliographical references and index.
Keywords: CHILDRENS LITERATURE